The impact of demographic factors and personality traits on nurse compassion fatigue: A cross-sectional analysis - Miao Zhao; Min Xie (PLoS ONE, 2025)
Background Compassion fatigue significantly impacts nurses’ work efficiency, care quality, and overall well-being. Consequently, the phenomenon of compassion fatigue among nurses has garnered considerable attention. Research from abroad indicates that demographic factors and the Big Five personality traits are closely related to the burnout dimension of compassion fatigue. This insight opens new avenues for studying compassion fatigue in nurses. Purpose This study aims to analyze the current state of compassion fatigue among nurses and its influencing factors. Furthermore, it seeks to explore the correlation between compassion fatigue and personality traits, providing valuable references for alleviating compassion fatigue among nurses. Methods A survey using general information, the Chinese Compassion Fatigue Short Scale, and the brief version of the Chinese Neuroticism Extraversion Openness Five-Factor Inventory was conducted on 332 nurses from a major tertiary hospital. Results The total score for nurse compassion fatigue was 51.83(SD=22.02). Factors such as years of service, professional title, monthly income, and department were identified as influencing compassion fatigue. The total score for compassion fatigue exhibited a negative correlation with extraversion, openness, agreeableness, and conscientiousness, while it showed a positive correlation with neuroticism. The Big Five personality traits accounted for 47.9%, 45.2%, and 50.2% of the variance in secondary trauma, burnout, and the overall compassion fatigue score, respectively. Conclusions/Implications for Practice Neuroticism and agreeableness are primary predictors of nurses’ compassion fatigue. Nursing managers can implement targeted measures to alleviate compassion fatigue based on the identified influencing factors and the predictive role of the Big Five personality traits.